2022
DOI: 10.3389/fmed.2022.910929
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of Gastroesophageal Reflux Disease and Functional Dyspepsia and Yield of Esophagogastroduodenoscopy in Patients Clinically Fulfilling the Rome IV Criteria for Functional Dyspepsia

Abstract: AimTo assess (1) the overlap rate of gastroesophageal reflux disease (GERD) and functional dyspepsia (FD) and (2) the yield of esophagogastroduodenoscopy in patients clinically presenting with FD.Materials and MethodsOutpatients aged ≥18 years with typical reflux symptoms ≥2 times a week or clinically fulfilling the Rome IV criteria for FD were recruited and underwent esophagogastroduodenoscopy. GERD was classified into non-erosive reflux disease (NERD) and erosive reflux disease (ERD), and FD was classified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…A study from United States reported no significant differences in age or gender among patients with GERD-FD overlap, GERD only, and dyspepsia only. 43 However, study from Vietnam indicated that older age were predominant in GERD-FD overlap, no gender and BMI difference was found, 11 female predominance were noted in FGIDs overlap patients in a study from South Korea. 44 A recent study indicated that waist-to-hip ratio but not BMI was a risk factor for GERD in Vietnamese patients.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A study from United States reported no significant differences in age or gender among patients with GERD-FD overlap, GERD only, and dyspepsia only. 43 However, study from Vietnam indicated that older age were predominant in GERD-FD overlap, no gender and BMI difference was found, 11 female predominance were noted in FGIDs overlap patients in a study from South Korea. 44 A recent study indicated that waist-to-hip ratio but not BMI was a risk factor for GERD in Vietnamese patients.…”
Section: Discussionmentioning
confidence: 87%
“… 9 Although there are separate guidelines for managing each disorder, FD-GERD overlap is very common by shared pathophysiology, including delayed gastric emptying and impaired gastric accommodation. 10 , 11 A meta-analysis review showed that 7.41% overlap between FD and GERD in the general population, and 31.32% FD with GERD symptoms. 10 Studies from Asia showed the prevalence of FD-GERD overlap is about 20.00-80.00% in different countries and regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the two studies included patients with either GERD or FD, with a primary focus on patients with FD. Though GERD and FD commonly overlap, they are different diseases and contain different pathophysiological etiologies [45,46]. Two studies on low-carbohydrate diets and one study on a low-FODMAP diet were included in the previous study, and these have also been included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…10 A study by Quach et al showed that FD-PDS is more prevalent among patients with FD-GERD overlap and NERD-FD overlap, causing more severe symptoms. 21 First-line treatment for GERD patients are acid-suppressive treatments such as PPIs or histamine H2-antagonists in conjunction with dietary and lifestyle modifications. Despite this, a considerable proportion of patients with some types of GERD do not experience symptomatic relief.…”
Section: Dilemma Between Fd and Gerd: Diagnostic And Treatment Consid...mentioning
confidence: 99%